(untitled) (Revista de História da UEG (REVHIST), 2019)
The present article seeks to study the chapters written by Lourenço de Brito Correia, wealthy man in Bahia and well-know serviceman in the bahian scene, against the General-Governor of the Estado do Brasil Diogo Luiz de Oliveira (1627 – 1635). The objective is to analyze the fundamental concepts that conceive the regime of Diogo Luiz as a tyran one according to the chapters author; besides discussing to what extent Lourenço’s biography enables a major understanding on the production of these forms of discourse with the positions he took in the Salvador’s political scene.